PENINGKATAN HASIL BELAJAR SISWA MELALUI MEDIA DOMINO MATEMATIKA (DOMIKA) PADA SISWA KELAS VIIA SMPN 1 CIKARANG BARAT - Mumpuni Mumpuni (STIT Islamic Village Tangerang, 2022)
The improvement of the quality of education can be seen from the achievements achieved by students, while the success of the achievement of mathematics learning results can be seen from the ability of students in solving integer operation problems correctly, although in general, not all students can solve integer operation problems, therefore it is expected that mathematical domino media (DOMIKA) can train students in performing calculation operations so that they are embedded in the carrying nature. conscious students. The purpose of this study is to find out the improvement of integer operation learning outcomes through mathematical domino media (DOMIKA) in students of class VII A SMPN 1 Cikarang Barat Bekasi Regency. This research includes a type of classroom action research (PTK), with its main characteristic being repeated actions and the main method is self-reflection aimed at improving learning. PTK is a problem-solving activity characterized by cyclic and reflection that starts from: a) planning, b) actions, c) observing, d) analyzing data/information to decide the extent of the advantages and disadvantages of such actions (reflecting). PTK is characterized by continuous improvement so that research satisfaction is often the benchmark of the cycle. In this first cycle, learning results were obtained with an average score of SMPN 1 Cikarang Barat students in Bekasi Regency of 69 and classically the completeness of student learning results was obtained by 65,625% with a frequency of 21 people out of 32 students present categorized as complete and 34,375% with a frequency of 11 people out of 32 students categorized as incomplete. From these results, it can be stated that the completeness of student learning to the maximum has not been achieved. In cycle II, learning results were obtained with the average score of SMPN 1 Cikarang Barat Students in Bekasi Regency of 80, and classically the percentage of completeness of the learning outcomes of SMPN 1 Cikarang Barat Bekasi Regency reached 93.75% with the number of frequencies of 30 people from 32 students present said to be complete and 6.25% with the number of frequencies of 2 people from 32 students categorized as unfinished. From these results, it can be stated that the application of mathematical domino learning media (DOMIKA) in cycle II is on target.